The Firmicutes/Bacteroidetes ratio of the human gut microbiota is associated with prostate enlargement - Takezawa, Kentaro; Fujita, Kazutoshi; Matsushita, Makoto; Motooka, Daisuke; Hatano, Koji; Banno, Eri; Shimizu, Nobutaka; Takao, Tetsuya; Takada, Shingo; Okada, Koichi; Fukuhara, Shinichiro; Kiuchi, Hiroshi; et al. (The Prostate, 2021)
Background The pathophysiology of the prostate enlargement underlying lower urinary tract symptoms is unknown. Meanwhile, the gut microbiota can contribute to various host conditions. We hypothesized that the gut microbiota plays a role in prostate enlargement. Methods We included 128 patients who underwent prostate biopsies at our hospitals between December 2018 and March 2020, excluding those who had used antibiotics within the past 6 months and those who were diagnosed with prostate cancer of cT3 or higher. Patients with prostate volumes ≥30 ml were defined as the prostate‐enlargement (PE) group; those with prostate volumes <30 ml were defined as the non‐PE group. Their gut microbiotas were analyzed via 16S rRNA metagenomic analyses of rectal swab samples and were compared between the groups. Results The PE group included 66 patients; the non‐PE group included 62 patients. Age, body mass index, and prostate‐specific antigen levels did not significantly differ between the groups. Linear discriminant analysis effect size analysis indicated a higher proportion of Firmicutes and Actinobacteria in the PE group and a higher proportion of Bacteroidetes in the non‐PE group. The Firmicutes/Bacteroidetes (F/B) ratio was significantly higher in the PE group than in the non‐PE group (2.21 ± 0.39 vs. 1.61 ± 0.40, p = 0.015). Conclusion The F/B ratio of the gut microbiota was associated with prostate enlargement. Although the detailed mechanisms are unclear, the gut microbiota might affect prostate enlargement.